‫اسرتاتيجية ‬‫التنبؤ‬ ‫المبيعات‬ في‬ ‫المؤسسة‬ ‫الاقتصادية‬ ‫دراسة‬ ‫حالة‬ ‫المؤسسة‬ ‫ الوطنية‬ ‫للدهن‬ ‫وحدة‬ ‫سوق‬ ‫أهراس‬ - عبد‬ ملالك ‫بوغان ‬‫‬; ‬‫سعد‫ بومعزة ‬ (My University, 2018)
Sales forecasting strategy is the process by which the organization takes consideration to address the future and development in business areas, and also to maintain its position in the business environment, particularly if it uses quantitative methods and applies the appropriate model in the process forecast. In our memory we will use the search method called BOX JENKINS and the exponential smoothing method in seasonal sales forecasting of the National Foundation for the Unity of SOUK-AHRAS and competent in various types paint production, using the SPSS 24 program, and also the program Eviews 8, then attempt to extract and analyze the results of both methods as those used and the results showed the convergence between the real values ​​of sales and values ​​which were predictable, and they are all located without exception in the domain of the forecast in the two methods that those used, to then be extracted the accuracy of these models and the possibility of reliable sales forecasting for periods and as a tool for us Business Sales Forecasting Strategy.